Rising damp in historic buildings: The wall base ventilation system - Ana Sofia Guimarães (2011)
This work intends to validate a new system fortreating rising damp in historic buildings walls. The resultsof laboratory experiments show that an efficient way oftreating rising damp is by ventilating the wall base, usingthe HUMIVENT technique. The analytical model presenteddescribes very well the observed features of risingdamp in walls, verified by laboratory tests, who contributedfor a simple sizing of the wall base ventilation system thatwill be implemented in historic buildings.